Survivalitas Harian Solopos di Era Konvergensi Media: Suatu Tinjaun Historis - Suryawati, Indah (Faculty of Da'wa and Communications Sciences, 2025)
Since the start (1997), Harian Solopos has been committed to being present as a local newspaper. The absence of local print media at that time was considered a business opportunity that should be capitalized on, given that no newspaper had ever been able to survive for long in the city of Solo. Harian Solopos appeared to break the myth of Solo as a